Ex vivo model of congenital cytomegalovirus infection and new combination therapies. Issue 1 (January 2015) - Morère, L.; Andouard, D.; Labrousse, F.; Saade, F.; Calliste, C.-A.; Cotin, S.; Aubard, Y.; Rawlinson, W.D.; Esclaire, F.; Hantz, S.; Ploy, M.-C.; Alain, S.
Abstract: Introduction: Congenital human cytomegalovirus (HCMV) infection is a major public health problem due to severe sequelae in the fetus and newborns. Currently, due to their toxicity anti-CMV treatments cannot be administered to pregnant women. We thus developed an ex vivo model of 1 st trimester placental CMV infection to observe the route of infection across the placenta and to test the efficacy of various new drugs targeting different stages of viral cycle. Methods: After validation of the viability of floating villi explants by ELISA β-HCG, the kinetics of placental infection were determined by immunochemistry and qPCR in this ex vivo model. Antiviral susceptibility was determined in vitro using focus reduction assay and by qPCR in the ex vivo model. Results: The ex vivo model showed viral infection in trophoblasts and mesenchymal space of floating villi. In vitro, antiviral combinations of maribavir with baïcalein or artesunate inhibited viral infection by more than 90%. On the other hand, in ex vivo model, infection was reduced by 40% in presence of maribavir and artesunate. The synergistic effect observed in vitro was not observed ex vivo . Discussion: This model allowed us to understand the CMV spread in 1 st trimester floating villi better and to analyze the anti-CMV efficacy and toxicity of new drugs that could be administered to pregnant women, either alone or in combination. Conclusions: Such an ex vivo model could be applied to other viruses such as rubella or parvovirus B19 and in new drug development. Highlights: The ex vivo model confirms the in situ spread of CMV from maternal blood via syncytiotrophoblasts. Tissue viability and viral load in explants confirm the validity of this model. An antagonistic effect was observed between artesunate/baïcalein in vitro and ex vivo . Maribavir and artesunate strongly inhibit the AD169 viral strain in vitro and ex vivo .